Upaya Guru Dalam Penerapan Pendidikan Karakter Di Pondok Pesantren Bai’aturridwan Bukittinggi - Khaira Ummah; Yasmi Anjeli; Nurhidayati Nurhidayati (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
Character education is education that shapes students' personalities which is related to moral education, where the aim is to shape and train individual abilities continuously in order to perfect themselves towards a better life. In its application, it requires the efforts or efforts of professional teachers in educating their students, where the teacher is a figure who is a role model for their students. This research aims to describe the various strategies used by teachers in implementing character education for students at the Bai'aturridwan Islamic boarding school in Bukittinggi.